Moral anthropology a critical reader - Fassin, Didier; Léze, Samuel (London Routledge/Taylor & Francis Group, 2014)
"This Reader is an essential resource for students and scholars interested in the anthropology of morality. The collection includes classical and more recent material, carefully chosen to provide a critical and historical overview of an important and developing field. The selections are contextualized with lucid editorial material, including a substantial introduction"-- Provided by publisher.
Keywords: Anthropological ethics